The impact of the left inferior frontal gyrus on fear extinction: A transcranial direct current stimulation study - Yuanbo Ma; Fujia Jiao; Giorgi Batsikadze; Fatemeh Yavari; Michael A. Nitsche (Brain Stimulation, 2024)
Introduction: Fear extinction is a fundamental component of exposure-based therapies for anxiety-related disorders. The renewal of fear in a different context after extinction highlights the importance of contextual factors. In this study, we aimed to investigate the causal role of the left inferior frontal gyrus (LiFG) in the context-dependency of fear extinction learning via administration of transcranial direct current stimulation (tDCS) over this area. Methods: 180 healthy subjects were assigned to 9 groups: 3 tDCS conditions (anodal, cathodal, and sham) × 3 context combinations (AAA, ABA, and ABB). The fear conditioning/extinction task was conducted over three consecutive days: acquisition, extinction learning, and extinction recall. tDCS (2 mA, 10min) was administered during the extinction learning phase over the LiFG via a 4-electrode montage. Skin conductance response (SCR) data and self-report assessments were collected. Results: During the extinction learning phase, groups with excitability-enhancing anodal tDCS showed a significantly higher fear response to the threat cues compared to cathodal and sham stimulation conditions, irrespective of contextual factors. This effect was stable until the extinction recall phase. Additionally, excitability-reducing cathodal tDCS caused a significant decrease of the response difference between the threat and safety cues during the extinction recall phase. The self-report assessments showed no significant differences between the conditions throughout the experiment. Conclusion: Independent of the context, excitability enhancement of the LiFG did impair fear extinction, and led to preservation of fear memory. In contrast, excitability reduction of this area enhanced fear extinction retention. These findings imply that the LiFG plays a role in the fear extinction network, which seems to be however context-independent.